Loss-of-function mutations in TGFB2 cause a syndromic presentation of thoracic aortic aneurysm. - Lindsay, Mark E; Schepers, Dorien; Bolar, Nikhita Ajit; Doyle, Jefferson J; Gallo, Elena; Fert-Bober, Justyna; Kempers, Marlies J E; Fishman, Elliot K; Chen, Yichun; Myers, Loretha; Bjeda, Djahita; Oswald, Gretchen; et al. (Nat Genet, 2012)
Loeys-Dietz syndrome (LDS) associates with a tissue signature for high transforming growth factor (TGF)-β signaling but is often caused by heterozygous mutations in genes encoding positive effectors of TGF-β signaling, including either subunit of the TGF-β receptor or SMAD3, thereby engendering controversy regarding the mechanism of disease. Here, we report heterozygous mutations or deletions in the gene encoding the TGF-β2 ligand for a phenotype within the LDS spectrum and show upregulation of TGF-β signaling in aortic tissue from affected individuals. Furthermore, haploinsufficient Tgfb2(+/-) mice have aortic root aneurysm and biochemical evidence of increased canonical and noncanonical TGF-β signaling. Mice that harbor both a mutant Marfan syndrome (MFS) allele (Fbn1(C1039G/+)) and Tgfb2 haploinsufficiency show increased TGF-β signaling and phenotypic worsening in association with normalization of TGF-β2 expression and high expression of TGF-β1. Taken together, these data support the hypothesis that compensatory autocrine and/or paracrine events contribute to the pathogenesis of TGF-β-mediated vasculopathies.
Keywords: Animals; Aortic Aneurysm, Thoracic; Disease Models, Animal; Female; Fibrillin-1; Fibrillins; Haploinsufficiency; Humans; Loeys-Dietz Syndrome; Male; Marfan Syndrome; Mice; Mice, Knockout; Mice, Mutant Strains; Microfilament Proteins; Mutation; Pedigree; Phenotype; Signal Transduction; Syndrome; Transforming Growth Factor beta2